Staying alive: Navigating water, gender and poverty inequalities in Kafr El Sheikh, Egypt - Joshi, Deepa; Lahham, Nisreen; Dessouki, Amina (International Water Management Institute, 2022)
The blog is on the results and findings of a CGIAR GENDER Platform supported project linked to the IWMI’s Rewater-Mena project aimed that analyzed the gender-power dynamics of irrigation at the tail ends of the drainage networks.